Preoperative hormone stimulation; does it increase hypospadias postoperative complications? - Fawzy, Mohamed; Marcou, Marios; Sennert, Michael; Wirmer, Johannes; Wullich, Bernd; T Hadidi, Ahmed (Journal of Pediatric Urology, 2023)
Aim of the study: To assess the effect of Preoperative Hormone Stimulation (PHS) on glans size in proximal hypospadias with chordee and small glans, and to determine if PHS is associated with increased postoperative complications. Patients & Methods: Between 2014 and 2021, 101 cases of proximal hypospadias with small glans (12 mm or less) were operated upon in our hospital and are the basis of this cohort. All patients underwent a standard two-stage surgical repair, undergoing a correction of the chordee in the first operation and urethroplasty in the second operation. All patients included were operated by the same surgeon. They were classified into two groups; Group A: 50 children were operated upon between 2014 and 2017 and did not receive PHS and Group B: 51 children operated between 2018 and 2021 and received PHS. Glans dimensions including Dorsal Longitudinal Length (DLL) and Glans Width (GW) were measured during the first operation. PHS was given 1–2 months before the second operation in Group B. The glans dimensions were measured again during the second operation after PHS. Follow up period ranged from 2 to 9 years (mean 5 years). Results: Following PHS a statistically significant increase in glans length (p = 0.042) and glans width (p = 0.011) was observed at the second operation, with 36 patients (70%) showing a mean glans width increase of 2.78 mm (range 2–8 mm) after receiving PHS. There was no statistically significant difference in the complication rates between the two groups (p = 0.556) with a fragility index of zero (FI = 0). Discussion: The present study separates itself from most other studies in the literature, in the fact that it has included only a specific group of proximal and perineal hypospadias with severe chordee and glans width of 12 mm or less and that glans dimensions were always objectively and accurately measured under general anesthesia. The other major difference is that PHS in our study was given after and not before the first operation. Furthermore, the fact that all patients prior to 2018 did not receive PHS and all patients after 2018 received PHS, indicates that there was no selection bias. Conclusion: This study shows that PHS results in an increase the size of the glans in 70% of patients with hypospadias and a small glans without an increase in postoperative complications.[Formula presented]
CRIS-Team Scopus Importer:2023-10-06
Keywords: Complications; Glans size; Hormone therapy; Hypospadias; Preoperative hormone stimulation; Preoperative hormone therapy